Evaluating basic motor competence in Italian children post-COVID-19 pandemic - Domenico Monacis; Dario Colella; Pierpaolo Limone (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2024)
Motor competence assessment represents one of the most important topics in the field of motor development and physical education. The present cross-sectional study aims to assess basic motor competence, self-perception and enjoyment during PA in a sample of normal weight and overweight-obese children post covid-19 pandemic. The sample (N= 107, age= 8-9 years old) was recruited from an experimental project in Lecce (Apulia). Motor competence assessment was conducted with MOBAK 3-4 protocol, and self-perception and enjoyment were evaluated with two validates questionnaires. Multivariate analysis of variance (MANOVA) has been performed to assess effect of gender and BMI on considered variables. Results from MANOVA showed significant main effect for gender [F(10,93) = 2.353, p= .013, η²= 0,218] and BMI cutoff [F(10,93) = 2.351, p= .013, η²= 0,218]. However, interaction effect was no significant. Moreover, independent t-test highlighted significant differences in catching, dribbling, balancing and object movement according to gender (p< .05), and in balancing, rolling and self-movement according to BMI cutoff (p< .05). Self-efficacy differed significantly between male and female. No effect was found for enjoyment. Further studies should investigate the effect of BMI and factors related to physical activity on motor competence development.